Game over, what now? : retirement challanges of professional athletes from Iceland - Egill Fjölnisson 2002- (2024)
Retiring from sports can have multiple consequences both mentally and physically on professional athletes while also bringing many changes to their everyday life. Although there have been many studies that have examined the diverse effect retirement has on professional athletes there have not been many on Icelandic athletes. The objective of this study was to examine the effect retirement has on former Icelandic professional athletes. This study used a qualitative method that involved semi-structured and unstandardized interviews to collect data on former professional athletes. The results showed that there were five themes, those were changes that occurred after retirement, reasons for retirement, the mental health of athletes before and after retirement, factors that helped the athletes transition into retirement, and the need for discussion about retirement among Icelandic athletes. It can be implied by these results that Icelandic professional athletes endure many diverse effects when it comes to retirement, most of them positive, and that there is a need for more discussion or some kind of help for retired athletes. Að leggja skóna á hilluna getur haft fjölbreytt áhrif bæði andlega og líkamlega á atvinnuíþróttamenn, ásamt því að hafa margvíslegar breytingar á líf þeirra. Þrátt fyrir að margar rannsóknir hafi verið gerðar sem skoða mismunandi áhrif ferlaloka á atvinnuíþróttamenn hafa ekki margar slíkar verið gerðar á íslenskum atvinnumönnum. Markmið rannsóknarinnar var að skoða hvaða áhrif ferlalok hafa haft á fyrrum íslenska atvinnumenn. Rannsóknin var eigindleg þar sem notast var við hálf uppbyggð og óstöðluð viðtöl til að safna gögnum um fyrrum íslenska atvinnumenn. Niðurstöður sýndu að það voru fimm þættir eða þemu sem þessir fyrrum íslensku atvinnumenn áttu sameiginlega þegar kom að ferlalokum. Þættirnir fimm voru breytingar sem gerast eftir ferlalok, ástæður fyrir ferlalokum, andleg líðan fyrir og eftir ferlalok, þættir sem hjálpaði þeim að í ferlinu við að leggja skóna á hilluna og þörf á meiri ...